Respuesta de Canthon indigaceus chevrolati Harold a las heces de bovinos tratados con lactonas macrocíclicas: Response of Canthon indigaceus chevrolati Harold to the feces of cattle treated with macrocyclic lactones - Rodríguez-Vivas, Roger Iván; Basto-Estrella, Gertrudis del S.; Reyes-Novelo, Enrique; Arcila-Fuentes, William; Ojeda-Chí, Melina Maribel; Trinidad-Martínez, Iris; Gutiérrez-Wong, Jazmín (Ecosistemas y Recursos Agropecuarios, 2020)
Macrocyclic lactones (ML) are antiparasitic drugs routinely used in tropical cattle farming. After its administration the drug is eliminated in the animal’s feces, causing a toxic effect on the beneficial fauna that provides ecosystem services, including the recycling of excrement to facilitate the return of nutrients to the grassland soil. Bioassays were carried out to determine the lethal and sublethal effect of feces from cattle treated with ivermectin (IVM-1% on a dose of 0.2 mg kg−1 l.w. and IVM-3.15% on a dose of 0.63 mg kg−1 l.w.) and moxidectin (MOX-1% on a dose of 0.2 mg kg−1 l.w. and MOX-10% on a dose of 1.0 mg kg−1 l.w.) on the dung beetle Canthon indigaceus chevrolati, an inhabitant species of tropical cattle systems. The feces of the treated animals were recovered at -1, 5, and 14 days post-treatment to be exposed to couples of C. i. chevrolati in the laboratory and determine its effect on the variables: number of nest balls built, number of imagoes that emerged, number of days to the emergence of imagoes, total grams of excrement consumed, and the proportion of emerged beetles in each of the different treatments evaluated. No lethal or sublethal effects were found in the different bioessays carried out. The results of this study suggest for the first time that this beetle is showing some type of tolerance (natural or induced) to IVM and MOX.